Applications of VAM-based equivalent beam model on effective performance of composite sandwich beam with M-shaped folded core - Zheng, Shi; Yifeng, Zhong; Qinshan, Yi; Xiaoquan, Liu (Composite structures, 2023)
The issue of facesheet-core debonding is expected to be addressed by increasing the bonding platform of the M-shaped folded core. To investigate its effective performance, the three-dimensional traditional equivalent beam (3D-TEB) model and the one-dimensional equivalent beam model (1D-EBM) of the M-shaped folded sandwich beam were established based on the variational asymptotic method. The expression of the original 3D elastic problem was given in variational form. By minimizing the energy functional, the asymptotic solutions of the warping functions and the Euler beam model (zeroth-order approximation) were obtained. Through the static and dynamic analysis of a three-dimensional folded sandwich beam and two equivalent beam models, the effectiveness of the 1D-EBM instead of the original 3D-TEB for static and dynamic analysis was verified. The influences of the location and frequency of the excitation on the dynamic performance of the CSB-MFC were investigated. Compared with 3D-FEM and 3D-TEM, the novelties of cell tailorability and local field recovery within the unit cell are very important features, which significantly facilitates the parametrical analysis of the CSB-MFC. The results showed that the change in the top width of the bonding platform had a particularly significant impact on the torsional stiffness. The wall thickness mainly affected the torsional performance, and the increase in the core height primarily improved the torsional and bending stiffness, resulting in the gradual increase in the fundamental frequency. •The VAM-based 1D-EBM is established to analyze the global response.•The accuracy of the model is verified by static and dynamic examples.•The influence of cell geometric parameters is systematically analyzed.•The dynamic performance of CSB-MFC is investigated based on the equivalent model.•The reduced DOFs of 1D-EBM result in high calculation efficiency.